2012
DOI: 10.1038/cdd.2012.140
|View full text |Cite
|
Sign up to set email alerts
|

Blebbishields, the emergency program for cancer stem cells: sphere formation and tumorigenesis after apoptosis

Abstract: Caspases mediate apoptosis and have also been implicated in stem-cell biology. How caspases are linked to stem-cell biology is not known. Here, we show that the apoptotic blebs of cancer cells fuse together to form novel structures called 'blebbishields'. Blebbishields form spheres by fusion. Both blebbishield formation and sphere formation involve active caspases and N-linked glycosylation. Sphere formation is enhanced by acidic pH and is counteracted by inhibitors of proton pump, caspases, and cholesterol. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(119 citation statements)
references
References 43 publications
4
113
1
1
Order By: Relevance
“…These spheres probably came from multiple cells fusion. 34,35 Those data suggests that CSCs expanded in those mammary cancer cell lines when cultured in electrospun PCL fibrous scaffolds. OCT3/4 and SOX2 function cooperatively to regulate their own transcription and the transcription of a large set of other genes, which control the self-renewal and pluripotency of stem cells.…”
Section: Cellular Morphology and Growth On Electrospun Pcl 3d Scaffoldsmentioning
confidence: 98%
“…These spheres probably came from multiple cells fusion. 34,35 Those data suggests that CSCs expanded in those mammary cancer cell lines when cultured in electrospun PCL fibrous scaffolds. OCT3/4 and SOX2 function cooperatively to regulate their own transcription and the transcription of a large set of other genes, which control the self-renewal and pluripotency of stem cells.…”
Section: Cellular Morphology and Growth On Electrospun Pcl 3d Scaffoldsmentioning
confidence: 98%
“…The early event of the apoptosis includes the exposure of phosphotidylserine on the cell membrane. The plasma membrane integrity is severely compromised during late apoptotic stages (45,46). The prostate cancer cells under the effect of the tropical plant extracts (in this work) showed the blabbing of outer wall of plasma membrane hinting toward the fact that apoptosis had already kickedoff.…”
Section: Discussionmentioning
confidence: 56%
“…1 We have found that cancer stem cells undergoing apoptosis can avoid cell death by evoking the 'blebbishield emergency program' to enter cellular transformation. 2,3 In the blebbishield emergency program, the first visual sign that indicates the course of apoptosis is being reversed is the construction of blebbishields from apoptotic bodies. 2 Blebbishield construction requires endocytosis and endocytosis-driven serpentine filopodia formation that tether the apoptotic bodies together and facilitate fusion ( Figure 1a).…”
mentioning
confidence: 99%
“…2,3 In the blebbishield emergency program, the first visual sign that indicates the course of apoptosis is being reversed is the construction of blebbishields from apoptotic bodies. 2 Blebbishield construction requires endocytosis and endocytosis-driven serpentine filopodia formation that tether the apoptotic bodies together and facilitate fusion ( Figure 1a). 2,3 Inhibition of dynamin-dependent endocytosis blocks the action of serpentine filopodia, inhibits blebbishield formation, and promotes apoptotic body formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation